Efeitos comportamentais e neuroquímicos induzidos pelo etanol em camundongos e suas relações com o sistema colinérgico e dopaminérgico - Martin, Ana Luíza de Aguiar Rocha (2011)
Ethanol is an agent with nonspecific action, which may interfere in various neurotransmitter systems. Atropine is an alkaloid with blocking action of the cholinergic system, used in cholinergic intoxication and other with cardiac involvement. The neuroleptic, haloperidol, is an antagonist of dopaminergic pathways, mainly by blocking the D2 receptor, used in the treatment of schizophrenia in both acute and chronic psychoses and maniac psychotic episodes. Several studies have reported the interaction between the dopaminergic and cholinergic pathway and their interaction separately with the ethanol. This study investigated the behavioral and neurochemical effects produced in the striatum induced by subchronic treatment with ethanol in presence and absence of atropine or haloperidol. Swiss mice were used, females, weighing between 25 - 30g. The animals were treated with distilled water (control), ethanol (1 or 3g/kg, po) or pre-treated with haloperidol (0.5 mg / kg, ip) or atropine (0.5 mg / kg, ip), this application was thirty minutes before administration of ethanol or distilled water daily for seven days. Thirty minutes after the last drug administration intraperitoneally or sixty minutes after the last oral administration, the animals were subjected to behavioral tests of open field and track rod (locomotors activity), hole board and plus maze (anxiety activity) and then sacrificed with dissection of the striatum for determination of monoamines (norepinephrine, dopamine and its metabolic acid 3, 4-dihydroxyphenylacetic) or the concentration of acetylcholinesterase. Ethanol showed a stimulating effect in depressing the lower dose and higher dose, especially in tests of locomotors activity. When associated with a higher dose, haloperidol showed, in most cases the potentiating effect of ethanol, since atropine in some tests only showed a tendency to reverse this effect only associated with ethanol at the lowest dose, although not observed in all parameters of evaluated. However, the effect produced a modest increase in the concentrations of dopamine in the striatum, but when associated with blockers, a reduction of these levels was more pronounced when the association was made with ethanol at the highest dose. In the evaluation of the enzyme acetylcholinesterase, all substances used, combined or not, reduced more than 60% levels this enzyme, being more evident in the administration of atropine alone, or the authorities which showed a significant reduction in the concentration of AD, also showed reduced AChE, showing the interaction of these two systems, suggesting them as possible targets of action of drug development which contribute to the treatment of alcoholism